Sustainable Cultural Tourism Development Strategy in Karuhun Eco Park Village, Sumedang Regency, West Java, Indonesia - Dewi Ratnasari; Waway Tiswaya; Riaman Riaman; Sukono Sukono; Rizki Apriva Hidayana; Grida Saktian Laksito (International Journal of Business, Economics, and Social Development, 2025)
The development of cultural arts tourism as a sustainable tourism destination is a priority considering the features and nature of these locations, which highlight a number of elements such the local economy, environment, culture, preservation, and community empowerment. One of the cultural tourism areas in Indonesia, to be precise the province of West Java, namely Kampung Ladang in Sumedang Regency which is located at the top of Pasir Peti hill - Marga Laksana Sumedang Village. Kampung Ladang is one of Sumedang's cultural tourism centres by collaborating with the local community to maintain and preserve traditional Sundanese culture and procedures, especially Sumedang culture and traditions. This research uses qualitative methods and uses IFAS / EFAS and SWOT Analysis which aims to identify the potentials developed by Kampung Ladang with data collection carried out by observation, indepth interviews, and documentaries. The results of this study indicate that Kampung Ladang has three potentials that are ready to be developed in attracting tourists to visit such as potentials that need to be improved, namely attractions and activities, external supporting potentials, namely accessibility infrastructure consisting of information boards and other supporting facilities, and potentials that are not yet available, namely the provision of tour packages through marketing and promotion strategies that can attract tourists to visit and can develop community-based sustainable tourism that is community-centred to improve community welfare, besides that government support is needed in carrying out development and maintenance. In order to meet the needs of travellers, businesses, the environment, and tourism management communities, among other stakeholders, sustainable tourism management is a type of tourism management that will play a significant role in both the present and the future economic and social conditions.